The effects of teacher–student reciprocity on students’ sense of belonging to the university; a moderated mediation model - Wang, Gao; Chen, Guiyun; Li, Bichun (Frontiers in Education, 2024)
Developing a pleasant and supportive emotional bond with teachers might help students feel more at home at school. However, research on the relationship between positive teacher–student relationships and students’ feelings of belonging in university settings is scarce. Using data from 426 student surveys, this study estimated the moderated mediation model which is generated based on attachment theory and reciprocity theory. As a result, teacher–student reciprocity increases students’ sense of belonging to the university, and teacher–student attachment moderates this effect. The effects of teacher-student reciprocity and teacher-student attachment on students’ sense of belonging to the institution are positively moderated by social group attachment. This work contributes to the study of the sense of belonging by expanding on the applications of attachment theory and reciprocity theory. This research has a practical application.